2022
DOI: 10.3390/jpm12060982
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning to Measure the Intensity of Indocyanine Green in Endometriosis Surgeries with Intestinal Resection

Abstract: Endometriosis is a gynecological pathology that affects between 6 and 15% of women of childbearing age. One of the manifestations is intestinal deep infiltrating endometriosis. This condition may force patients to resort to surgical treatment, often ending in resection. The level of blood perfusion at the anastomosis is crucial for its outcome, for this reason, indocyanine green (ICG), a fluorochrome that green stains the structures where it is present, is injected during surgery. This study proposes a novel m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
(80 reference statements)
0
5
0
Order By: Relevance
“…In their study, Hernández et al qualitatively confirmed the value of intraoperative indocyanine use to predict fistula formation in full-thickness intestinal resection and re-anastomosis due to insufficient vascularization of the anastomosis site, with a sensitivity and specificity of 100%. However, the obtained results in this field are still inconsistent and there is a need for larger studies with a larger sample size ( 35 , 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…In their study, Hernández et al qualitatively confirmed the value of intraoperative indocyanine use to predict fistula formation in full-thickness intestinal resection and re-anastomosis due to insufficient vascularization of the anastomosis site, with a sensitivity and specificity of 100%. However, the obtained results in this field are still inconsistent and there is a need for larger studies with a larger sample size ( 35 , 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…In their observational study, the authors used DL-algorithms to quantify the level of indiocyanine green, and consequently of blood perfusion, in bowel anastomoses during laparoscopic bowel resection for endometriosis. The model obtained 92% accuracy and may represent a first step towards the adoption of AI in surgical settings to increase precision and reduce the frequency of complications [91].…”
Section: Role In Surgical Treatmentmentioning
confidence: 94%
“…In their observational study, the authors used DL algorithms to quantify the level of indiocyanine green, and consequently of blood perfusion, in bowel anastomoses during laparoscopic bowel resection for endometriosis. The model obtained 92% accuracy and may represent a first step towards the adoption of AI in surgical settings to increase precision and reduce the frequency of complications [89].…”
Section: Role In Surgical Treatmentmentioning
confidence: 94%